2020
DOI: 10.1016/j.jbiomech.2019.109486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a passive back exoskeleton on the mechanical loading of the low-back during symmetric lifting

Abstract: Low-back pain is the number one cause of disability in the world, with mechanical loading as one of the major risk factors. Exoskeletons have been introduced in the workplace to reduce low back loading. During static forward bending, exoskeletons have been shown to reduce back muscle activity by 10% to 40%. However, effects during dynamic lifting are not well documented. Relative support of the exoskeleton might be smaller in lifting compared to static bending due to higher peak loads. In addition, exoskeleton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 42 publications
8
45
1
Order By: Relevance
“…Lumbar flexion angles with these exos typically changed by less than 8° relative to not wearing an exo. They did observe a slight reduction (7%) in trunk velocity during lifting when wearing one of the two back exos tested, which was qualitatively consistent with Koopman et al (2020a) who observed an 18% reduction in peak trunk velocity while wearing the same exo. Almosnino et al (2021) also found that the time to reach peak trunk flexion was slightly delayed when wearing a rigid back exo, but concluded that it did not alter inter-segmental coordination of the pelvis-trunk during lifting.…”
Section: The Need and Benefit Of Keeping Ergonomic Assessment Tools As Simple As Practicalsupporting
confidence: 84%
See 1 more Smart Citation
“…Lumbar flexion angles with these exos typically changed by less than 8° relative to not wearing an exo. They did observe a slight reduction (7%) in trunk velocity during lifting when wearing one of the two back exos tested, which was qualitatively consistent with Koopman et al (2020a) who observed an 18% reduction in peak trunk velocity while wearing the same exo. Almosnino et al (2021) also found that the time to reach peak trunk flexion was slightly delayed when wearing a rigid back exo, but concluded that it did not alter inter-segmental coordination of the pelvis-trunk during lifting.…”
Section: The Need and Benefit Of Keeping Ergonomic Assessment Tools As Simple As Practicalsupporting
confidence: 84%
“…EMG is a great tool for research but is difficult to use as the basis for accessible, scalable, practical ergonomic assessment, particularly for the back. To briefly summarize key challenges: (i) EMG requires considerable time and expertise to collect and process (Besomi et al, 2020), and as such this level of analysis is not accessible or affordable for most safety professionals; (ii) there are an abundance of back extensor muscles, many of which are not measurable with surface EMG, meaning EMG studies only capture a subset of back muscle behaviors; (iii) there is substantial inter-subject variability with respect to which back muscles individuals offload and in what proportion when exo assistance is provided (Lamers et al, 2020), meaning it is unclear which subset of muscles to measure or how to make equitable comparisons between different individuals or exos; (iv) EMG only captures changes in muscle activity, and fails to capture reductions in spinal ligament loading (e.g., during stooped bending); (v) the relationship between EMG and force is non-linear, and dependent on other factors like muscle length, contraction velocity, electrode placement, and body posture (Ranavolo et al, 2020;Trinler et al, 2018), which can confound exo vs. no exo comparisons if kinematics are not tracked or controlled (Koopman et al, 2020a;Lamers et al, 2020); (vi) there can be safety concerns with normalization procedures that require maximum contractions (Cholewicki et al, 2011); and (vii) there is within-and betweenparticipant variability when measuring EMG (e.g., due to motion artifacts, tissue conductivity) even without exos (Cholewicki et al, 2011), which can introduce reliability or interpretation issues, and these must be overcome with rigorous experimental design and data processing (Besomi et al, 2020).…”
Section: The Need and Benefit Of Keeping Ergonomic Assessment Tools As Simple As Practicalmentioning
confidence: 99%
“…Research papers and projects focus mainly on the technical details of parts and assemblies as well as analysing the biomechanical movements of the user and the corresponding exoskeleton (Toxiri et al, 2018b;Yong et al, 2019). Recently, studies regarding the effectiveness and the potential of exoskeletons are published as well (de Vries and Bosch et al, 2016;Fox et al, 2019;Theurel and Desbrosses, 2019;Koopman et al, 2020). 2018) describe a method for the digital examination of prototypes at the workplace and especially for the coupling of the CAD exoskeleton with a digital humanoid in a digital workplace.…”
Section: Analysing Existing Methods In Developing Exoskeletonsmentioning
confidence: 99%
“…In addition, the devices reduce the intradiscal pressure with the longer moment arm of the bands compared to the spinal muscles. Other previous exoskeletons, such as Laevo [22]- [24] and the Bending Non-Demand Return (BNDR) [25], [26], possess spring-like elements placed around the hip joints, which provide extensor moments and reduce the moment that the lower back muscles have to counteract on when bending, thereby reducing lower muscle activation and intervertebral pressure.…”
Section: Introductionmentioning
confidence: 99%